Collaborative environmental governance frameworks a practical guide - Gieseke, Timothy M. (CRC Press, 2020)
"This book takes a practical approach to understanding and describing collaborative governance for resolving environmental problems. It introduces a new collaborative governance assessment model and recognizes that collaborations are a natural result of organizations converging around complex issues. Rather than identifying actors by their type of organization, the actors are identified by the type of role they play. This approach is aligned with how individuals and organizations interact in practice, and their dependance on collaborations to solve emerging environmental problems. The book discusses real cases with governance issues and creates new frameworks for collaborations"--